Ethanol upregulates the P2X7 purinergic receptor in human macrophages. (3rd December 2018) - Le Daré, Brendan; Victoni, Tatiana; Bodin, Aude; Vlach, Manuel; Vene, Elise; Loyer, Pascal; Lagente, Vincent; Gicquel, Thomas
Abstract: Alcohol consumption is considered to be the third leading cause of death in the United States. In addition to its direct toxicity, ethanol has two contrasting effects on the immune system: the nucleotide oligomerization domain‐like receptor pyrin domain‐containing‐3 (NLRP3) inflammasome is inhibited by acute ethanol exposure but activated by chronic ethanol exposure. Purinergic receptors (especially the P2X7 receptor) are able to activate the NLRP3 inflammasome and are involved in many ethanol‐related diseases (such as gout, pulmonary fibrosis, alcoholic steatohepatitis, and certain cancers). We hypothesized that ethanol regulates purinergic receptors and thus modulates the NLRP3 inflammasome's activity. In experiments with monocyte‐derived macrophages, we found that interleukin (IL)‐1β secretion was inhibited after 7 h of exposure (but not 48 h of exposure) to ethanol. The disappearance of ethanol's inhibitory effect on IL‐1β secretion after 48 h was not mediated by the upregulated production of IL‐1β, IL‐1α, IL‐6 or the inflammasome components NLRP3, apoptosis‐associated speck‐like protein containing a caspase recruitment domain, and caspase 1. P2X7R expression was upregulated by ethanol, whereas expression of the P2X4 and P2X1 receptors was not. Taken as a whole, our results suggest that ethanol induces NLRP3 inflammasome activation by upregulating the P2X7 receptor. This observation might have revealed a new mechanism for inflammation in ethanol‐related diseases.